Diagnosis of primary lung cancer and benign pulmonary nodules: a comparison of the breath test and 18F-FDG PET-CT - Ding, Xiangxiang; Lin, Guihu; Wang, Peiyu; Chen, Haibin; Li, Nan; Yang, Zhi; Qiu, Mantang (Frontiers in Oncology, 2023)
With the application of low-dose computed tomography in lung cancer screening, pulmonary nodules have been widely detected. Discrimination between primary lung cancer and benign nodules is a major clinical challenge. In the current study, we investigated whether exhaled breath could be used for diagnoses of pulmonary nodules and compared the breath test with 18F-FDG PET-CT. Exhaled breath was collected by Tedlar bags and analyzed by high-pressure photon ionization time-of-flight mass spectrometry (HPPI-TOFMS). A retrospective cohort (n=100) and a prospective cohort (n=63) of patients with pulmonary nodules were established. In the validation cohort, the breath test achieved an area under curve AUC of 0.872 (95% CI 0.760-0.983) and a combination of 16 volatile organic compounds among breathomics achieve an AUC of 0.744 (95% CI 0.7586-0.901). For PET-CT, SUVmax alone had an AUC of 0.608 (95% CI 0.433-0.784) while after combining with CT image features, 18F-FDG PET-CT had an AUC of 0.821 (95% CI 0.662-0.979). This study showed that a breath test based on HPPI-TOFMS is effective for discriminating lung cancer from benign pulmonary nodules and it had similar accuracy with 18F-FDG PET-CT.